SOSIALISASI MITIGASI BENCANA INKLUNSIF: MEWUJUDKAN DUSUN GERUPUK YANG TANGGUH BENCANA Nunik Cokrowati1, Mardiatul Husna2, Prasetyo Fajar Islam3, Muhammad Arif Ramadhan4, Beuty Asya5, Rivaldi Ananda Saputra6, Rosalina7, Devita Safira8, Riatulhilal9, Nulia - Cokrowati, Nunik; Husna, Mardiatul; Islam, Prasetyo Fajar; Ramadhan, Muhammad Arif; Asya, Beuty; Saputra, Rivaldi Ananda; Rosalina; Safira, Devita; Riatulhilal; Aprilia, Nulia Angga; Aimin, Almu (Universitas Mataram, 2024)
Gerupuk Hamlet, which is 100 m from the sea, is at great risk of natural disasters, especially tsunamis. Therefore, the Gerupuk Hamlet community's understanding of inclusive disaster mitigation is a necessity. Therefore, the Sengkol II Village KKN Team and TSBD conducted outreach regarding disaster recognition, prevention, disaster mitigation (evacuation routes and safe points), and disaster preparedness. This socialization was carried out with the aim of increasing the knowledge and understanding of the Gerupuk Hamlet community regarding disaster mitigation so that the community becomes more responsive to the disaster risks they face. The socialization method used is presentation of material and practice of making evacuation route maps along with disaster safe points. The socialization was considered successful because the participants who attended exceeded the target, namely 37 people. Apart from that, the people of Gerupuk Hamlet are increasingly aware of disaster mitigation through the outreach carried out. This is proven by the community's ability to create maps of evacuation routes and disaster safe points after presenting the material.